ZMIANY POWIERZCHNI I ZARASTANIE JEZIOR W POLSCE - CHOIŃSKI, ADAM; SKOWRON, RAJMUND (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2022)
The paper presents changes in the surface area and overgrowing of the largest Polish lakes (> 500 ha). It has been established (on the basis of 4 analyzed time sequences) that over the last 80 years there has been a gradual reduction of the lake area. At the same time, the area occupied by emerged vegetation has increased. This is confirmed by the lake overgrowth rate and the shoreline overgrowth rate.